Original parts: Aging and reckoning with cystic fibrosis related kidney disease - Alexandra Nowakowski (The Beryl Institute, 2018)
Kidney disease increasingly impacts people with cystic fibrosis (CF) as adult patients continue to survive longer. Yet the literature on CF related kidney disease focuses little on amplifying the voices of people aging with the condition. This article presents perspectives on CF related kidney disease from a medical sociologist who is themselves managing these issues. It (1) gives an overview of relevant literature and trends in epidemiological data on kidney disease and CF, (2) details the author's own process of adjusting to progressive changes in renal function, and (3) outlines opportunities for clinicians to make a positive impact for patients by centering their voices.